Low biodiversity state persists two decades after cessation of nutrient enrichment. (10th January 2013) - Isbell, Forest; Tilman, David; Polasky, Stephen; Binder, Seth; Hawthorne, Peter; Rejmanek, Marcel
Abstract Although nutrient enrichment frequently decreases biodiversity, it remains unclear whether such biodiversity losses are readily reversible, or are critical transitions between alternative low‐ and high‐diversity stable states that could be difficult to reverse. Our 30‐year grassland experiment shows that plant diversity decreased well below control levels after 10 years of chronic high rates (95–270 kg N ha−1 year−1) of nitrogen addition, and did not recover to control levels 20 years after nitrogen addition ceased. Furthermore, we found a hysteretic response of plant diversity to increases and subsequent decreases in soil nitrate concentrations. Our results suggest that chronic nutrient enrichment created an alternative low‐diversity state that persisted despite decreases in soil nitrate after cessation of nitrogen addition, and despite supply of propagules from nearby high‐diversity plots. Thus, the regime shifts between alternative stable states that have been reported for some nutrient‐enriched aquatic ecosystems may also occur in grasslands.